2017
DOI: 10.1002/jctb.5487
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous sequestration of nitrate and phosphate from wastewater using a tailor‐made bacterial consortium in biofilm bioreactor

Abstract: BACKGROUND Municipal wastewater usually contains nitrate and phosphate as major contaminants, and if discharged untreated affects the health of the environment and human population. Currently available treatment technologies to treat municipal wastewater lose the essential growth nutrients ‘P’ and ‘N’ during treatment. This paper presents a strategy of simultaneous sequestration of nitrate and phosphate in biomass, by using a tailor‐made consortium in a biofilm reactor. RESULTS The consortium comprising of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The enzyme production by the consortium under suspended and immobilized conditions was similar. As stated in the literature, this finding again reconfirms that immobilization either enhances or maintains system performance [ 32 ]. Also, it protects the microbes from external perturbations.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The enzyme production by the consortium under suspended and immobilized conditions was similar. As stated in the literature, this finding again reconfirms that immobilization either enhances or maintains system performance [ 32 ]. Also, it protects the microbes from external perturbations.…”
Section: Resultssupporting
confidence: 84%
“…Bacteria survive better in an environment as consortium than pure isolate [ 32 ] (during synergistic interaction), resulting in better performance through production of desired enzyme combination [ 28 ]. In this study, two well-characterized bacterial strains, viz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Municipal wastewater contains phosphate, nitrate and other contaminants which mainly discharged directly to the environment without any treatment severely affects ecosystem and the health of human population ( Saha et al, 2018 ). The composition of wastewater is highly complex and it contains mixture of highly complex molecules, which affect biodegradation process ( Heidrich et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional phosphorous removal technologies include the utilization of a variety of chemical and biological processes. Recent studies on biological technologies targeting the removal of phosphates from aqueous solutions reported on the use of engineered environmental bacteria [4] and specifically grown bacterial consortia in biofilm bioreactors [5], as well as on the introduction of shifts in structure and functions of microbial communities [6]. Studies also reported on the introduction of supplemental materials [7,8] or specific bacterial species [9] to activated sludge aerobic reactors that enhanced phosphates removal.…”
Section: Introductionmentioning
confidence: 99%